The problem of overlapping curricula in criticism Cinematographic discourse (Journal of the College of Basic Education, 2023)
In the last decade, individuals have become so weak and unwell that we cannot resistTheir bodies are exposed to diseases that make them feel irritable, and this is what stimulated themresearcher for the study; Where the study aimed to identify the impact of the proposed training programIn some immunological blood indicators (177130, 180, 1814) and depression in women of all ages(25-40) years old, and the researcher used the experimental method for one group on a communityIt consisted of (21) women who suffered from a deficiency in the level of immunological blood indicatorsThe study and after excluding the participants in the exploratory experiment and the non-regulars in the trainingThe final sample number has become (20) women, and the sample has been subjected to pre-tests in terms of filling inDepression scale form, then the training program was implemented, which lasted (16) weeks(2) Training units per week, as the duration of the training unit took (06) minutes, and after the endIn the training program, the researcher conducted post-tests, which included examining indicatorsThe immunological blood is being studied and the depression scale form is filled out, and after the results are collected, they are processedStatistically, the researcher concluded that the proposed training program made a positive development in theThe improvement of the immunological indicators under study, and thus the improvement of the state of depression among a sampleTherefore, the researcher recommends adopting the application of the proposed training program when designing programsTraining and health because of its positive impact on improving the level of immune indicators and moodIndividuals, as well as encouragement to engage in various sports activities and physical fitness curriculaAnd health in sports and social institutions and clubs.